2019
DOI: 10.1017/s0263574719001425
|View full text |Cite
|
Sign up to set email alerts
|

Collision Detection on Industrial Robots in Repetitive Tasks Using Modified Dynamic Time Warping

Abstract: SUMMARYThis paper presents a non-model-based collision detection algorithm for robots without external sensors and with closed control architecture. A reference signal of repetitive motion is recorded from the robot operation. To detect collisions, the reference is compared with measurements from the robot. One of the key contributions is a novel approach to optimal matching of compared signals, which is ensured by the newly developed modified Dynamic Time Warping (mDTW) method presented in this paper. One of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In industrial robotics, signals available at the level of robot joint usually include current values, joint angles, and in some cases torques or their estimated values. Previous research and analysis of the available signal properties [ 12 , 13 , 31 ] has observed that the measurements of currents and torque estimations are repeatable for similar movements, but that sampling is often inconsistent due to a lack of true parallel-processing capabilities.…”
Section: Underlying Ideamentioning
confidence: 99%
See 3 more Smart Citations
“…In industrial robotics, signals available at the level of robot joint usually include current values, joint angles, and in some cases torques or their estimated values. Previous research and analysis of the available signal properties [ 12 , 13 , 31 ] has observed that the measurements of currents and torque estimations are repeatable for similar movements, but that sampling is often inconsistent due to a lack of true parallel-processing capabilities.…”
Section: Underlying Ideamentioning
confidence: 99%
“…As a result, they are now offering different Industry 4.0 functionalities, connectivity, and simulation-related options, at least for their new and upcoming products [ 3 ]. Furthermore, related topics that have made undisputedly valuable contributions to novel industrial concepts are: collision detection and avoidance [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], physical human–robot interaction [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], kinesthetic guidance [ 19 , 20 , 26 ], motion planning, digital twins, augmented reality, and facilitated programming.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The output of the rule-base model and other conventional inputs are provided to the Sugeno fuzzy model, and the effective steering angle is used as the final output to avoid obstacles existing in the environment and safely guide the humanoid robot to the target point. Gordic and Jovanovic et al [6] develops two complementary decision rules to identify conflicts.…”
Section: Introductionmentioning
confidence: 99%